In vitro culture and phenotypic and molecular characterization of gastric stem cells from human stomach. Issue 2 (4th September 2016) - Garcia, Magali; Chomel, Jean‐Claude; Mustapha, Pascale; Tran, Cong Tri; Garnier, Martine; Paris, Isabelle; Quellard, Nathalie; Godet, Julie; Cremniter, Julie; Bennaceur‐Griscelli, Annelise; Lecron, Jean‐Claude; Turhan, Ali G.; et al.
Abstract: Background: Human gastric mucosa shows continuous self‐renewal via differentiation from stem cells that remain poorly characterized. Methods: We describe an original protocol for culture of gastric stem/progenitor cells from adult human stomach. The molecular characteristics of cells were studied using TaqMan low‐density array and qRT‐PCR analyses using the well‐characterized H1 and H9 embryonic stem cells as reference. Epithelial progenitor cells were challenged with H. pylori to characterize their inflammatory response. Results: Resident gastric stem cells expressed specific molecular markers of embryonic stem cells (SOX2, NANOG, and OCT4), as well as others specific to adult stem cells, particularly LGR5 and CD44. We show that gastric stem cells spontaneously differentiate into epithelial progenitor cells that can be challenged with H .  pylori . The epithelial progenitor response to H. pylori showed a cag pathogenicity island‐dependent induction of matrix metalloproteinases 1 and 3, chemokine (CXCL1, CXCL5, CXCL8, CCL20) and interleukine 33 expression. Conclusion: This study opens new outlooks for investigation of gastric stem cell biology and pathobiology as well as host– H. pylori interactions.